Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2006)
This paper provides a semi-annual review of the status of financing for PRGFESF lending, HIPC-MDRI debt relief, and subsidization of emergency assistance to PRGF-eligible members. The last update was issued to the Executive Board in March 2006.